2017
DOI: 10.5539/ijel.v7n6p78
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metadiscourse Features in Argumentative Writing by Pakistani Undergraduate Students

Abstract: Metadiscourse involves the interaction between the reader and the writer of the text in the overall process of communication. Metadiscourse not only guides the reader to understand the primary message of the text through structure and content, but also it intimates the reader with the particular slants and perspectives in the primary discourse. The students have to master the use of Metadiscourse in their writings. The purpose of this study is to examine the distribution and frequency of Metadiscourse features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
2
1
1
Order By: Relevance
“…Contrary to what have been found in previous studies on L2 writers, the study conducted by Heng and Tan (2010) revealed that the corpus of argumentative essays written by Malaysian undergraduate students exhibited more interactional metadiscourse markers rather than interactive metadiscourse markers. Similar to Heng and Tan's (2010) findings mentioned above, Mahmood, Javaid and Mahmood (2017) found that Pakistani undergraduate students were more inclined to using interactional metadiscourse markers instead of interactive ones in their argumentative essays. Nevertheless, in both studies, 'transitions' which is one of the subcategories of interactive metadiscourse, was the most frequently used type of metadiscourse by L2 learners.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Contrary to what have been found in previous studies on L2 writers, the study conducted by Heng and Tan (2010) revealed that the corpus of argumentative essays written by Malaysian undergraduate students exhibited more interactional metadiscourse markers rather than interactive metadiscourse markers. Similar to Heng and Tan's (2010) findings mentioned above, Mahmood, Javaid and Mahmood (2017) found that Pakistani undergraduate students were more inclined to using interactional metadiscourse markers instead of interactive ones in their argumentative essays. Nevertheless, in both studies, 'transitions' which is one of the subcategories of interactive metadiscourse, was the most frequently used type of metadiscourse by L2 learners.…”
Section: Literature Reviewsupporting
confidence: 81%
“…On the other hand, this was different with the study on L2 writers by Heng and Tan (2010), where the study had revealed that Malaysian undergraduate students produced more interactional metadiscourse markers than interactive metadiscourse markers in their argumentative essays. Interestingly, Mahmood, Javaid & Mahmood (2017) also found that Pakistani undergraduate students were more inclined in using interactional metadiscourse markers instead of interactive ones in their corpus of argumentative writings in which is similar to the findings by Heng and Tan (2010). Transition Markers were found as the most frequently used features by L2 learners.…”
Section: Previous Studiessupporting
confidence: 85%
“…In overall, both courses used more interactive metadiscourse features (2964) than interactional metadiscourse features (1777) in their writings. In general, both courses employed more interactive metadiscourse features than interactional metadiscourse features in their writings which is similar to the result by Alkhathlan (2019), but somehow different with studies by Heng and Tan (2010) and Mahmood et. al (2017) who revealed that undergraduate students' L2 corpus exhibited more interactional metadiscourse features rather than interactive metadiscourse features.…”
Section: Resultscontrasting
confidence: 44%
“…In Malaysian context, the study on L2 writers by Heng and Tan (2010) had revealed that Malaysian undergraduate learners produced more interactional metadiscourse markers than interactive metadiscourse markers in their argumentative essays. Interestingly, Mahmood et. al (2017) also found that Pakistani undergraduate learners were more inclined in using interactional metadiscourse markers instead of interactive ones in their corpus of argumentative writings.…”
Section: Previous Studiesmentioning
confidence: 99%